Sequences of Trypsin Inhibitor Gene on Jatropha curcas L. Issue 1 (May 2021) - Primandiri, P R; Amin, M; Zubaidah, S; Maftuchah,; Santoso, A M
Abstract: Trypsin Inhibitor ( TI ) is one of unique gene which involved in plant protection from biotic and abiotic defense. The exploration variation of TI gene sequence is crucially needed asbasic reference, especially in J. curcas to support national biodiesel production. TI gene in J. curcas has been successfully isolated and sequenced form some crossed numbers (number 5 (SP-8 X SP-16), 6 (SP-8 X SP-38), 7 (SP-33 X HS-49), and 18 (SM-35 X SP-38) of J. curcas . Fourth sequence samples compared with two prime accessions (IP3A and IP3P). TI gene was successfully isolated, sequensed (598-604 bp), and aligned using BioEdit Sequence Alignment Editor 7.2.5 program. There were insertion and substitutionthat occur in all samples that lead to differences TI gene sequences. There are 11 siteswas inserted. Sample 18 and 7 only inserted at one site only. Substitution has been occured at 14 sites, 35.71% (5 sites) as transition and 64.29% as transvertion. Both ofinversion and substitution in some sites leads to change in the proportion of nucleic acid ofTI genes. Further analysis is needed to determine the impact of IT gene variation on J. curcas physiological response in environmental defense.